AB0740 USE OF SECUKINUMAB IN PATIENTS WITH PSORIATIC ARTHRITIS. IMPACTS OF COMBINATION WITH METHOTREXATE. (June 2019) - Choquette, Denis; Bessette, Louis; Sauvageau, Loïc Choquette; Ferdinand, Isabelle; Haraoui, Paul; Massicotte, Frédéric; Pelletier, Jean-Pierre; Raynauld, Jean-Pierre; Rémillard, Marie-Anaïs; Sauvageau, Diane; Villeneuve, Édith; Coupal, Louis
Abstract : Background: Secukinumab (SECU) is a human IgG1κ monoclonal antibody that binds to the protein interleukin-17A approved for the treatment of psoriasis, ankylosing spondylitis, and psoriatic arthritis (PsA). Recently presented data suggest that combination with methotrexate (MTX) in patients with PsA may not be as necessary as in rheumatoid arthritis as it improves neither efficacity nor sustainability (1, 2, 3, 4). Objectives: This analysis describes the use of SECU with or without MTX. Methods: The data of patients with psoriatic arthritis seen since January 1, 2015 (date at which SECU appeared in the Canadian market) at the Institut de Recherche en Rhumatologie de Montréal (IRRM) and the Centre de l'Ostéoporose et de Rhumatologie de Québec (CORQ) was extracted from the Rhumadata® clinical database and registry on January 7, 2019. Selected patients initiated SECU either without (MTX-) or with MTX (MTX+). The collected data include baseline characteristics (socio-demographic variables, concomitant and past medication, comorbidities and the Charlson comorbidity index (CCI)), variables measured over time (laboratory test results, patient and physician-reported outcomes, and disease activity measures such as minimal disease activity (MDA), CDAI and DAS28(4)-ESR) and persistence data (treatment duration, reason for cessation). The groups were compared to identify potential confounder, and persistence data were analyzed using Kaplan-Meier and proportional hazard methods. Results: A total of 96 patients were prescribed SECU since January 1, 2015. Of those, 49% (n=47) treated with MTX. No significant differences in baseline (at treatment initiation) were observed between the MTX+ and MTX- groups. Average age at treatment initiation was 52.4 (standard deviation=11.3) and 53.7 (13.4) in the MTX+ and MTX- groups respectively. Women represent 45% and 55% of these groups, and the average body mass index was 29.9 (6.2) and 28.1 (6.0) kg/m2. Patient global, pain and fatigue assessments, made on a visual analogue scale ranging from 1 to 10, were 4.9 (2.6), 5.3 (2.9) and 4.3 (2.9) in the MTX+ group and 6.3 (2.2), 6.9 (2.1) and 6.5 (2.9) in the MTX- group. Among the 38 (40%) patients ceasing therapy, the principal reason for cessation was "inefficacy" (MTX+: 15/17 (88%) vs MTX-: 15/21 (71%)). Patients remaining on treatment at last follow-up had an average treatment duration of 1.7 (0.8) and 1.5 (0.7) years. The improvement in CDAI, HAQ and the percentage of patients reaching MDA are similar for both groups. No difference in retention was observed between the MTX+ and MTX- groups (log-rank p=0.4867). These results remain unchanged when we adjust for age at treatment initiation, gender, disease duration, and comorbidities (Charlson comorbidity index). Conclusion: Combining MTX to SECU does not improve its sustainability over time. Efficacy was also the same for both cohorts. References: [1] Mease PJ, et al. Arthritis Rheumatol. 2018; 70 (suppl 10). Abstract L11 [2] Benryane O, et al. Arthritis Rheumatol. 2018; 70 (suppl 10). Abstracts 693 and 694 [3] Benryane O, et al. CRA-2019, Montréal, Canada. Disclosure of interests: Denis Choquette Grant/research support from: abbvie, amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Consultant for: abbvie, amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Speakers bureau: abbvie, amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Louis Bessette Grant/research support from: abbVie, amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer inc, Roche, Sanofi, UCB, Consultant for: abbVie, Celgene, Eli Lilly, Novartis, Pfizer inc, Loïc Choquette Sauvageau: None declared, Isabelle Ferdinand Consultant for: abbVie, amgen, Novartis, Pfizer, Speakers bureau: amgen, Pfizer, Paul Haraoui Grant/research support from: abbvie, amgen, Pfizer, UCB, Consultant for: abbvie, amgen, Lilly, Pfizer, Sandoz, UCB, Speakers bureau: Pfizer, Frédéric Massicotte Consultant for: abbVie, Pfizer, Janssen, Eli Lilly, Speakers bureau: Janssen, Jean-Pierre Pelletier Shareholder of: Shareholder in arthroLab inc., Grant/research support from: Study funded by TRB Chemedica SA, Consultant for: TRB Chemedica SA, Jean-Pierre Raynauld Consultant for: arthroLab inc., Marie-Anaïs Rémillard Consultant for: abbvie, amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Paid instructor for: abbvie, amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Speakers bureau: abbvie, amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Diane Sauvageau: None declared, Édith Villeneuve Consultant for: abbVie, UCB, Celgene, Roche, Pfizer, amgen, BMS, Sanofi-Genzyme, Paid instructor for: abbVie, Speakers bureau: abbVie, Pfizer, BMS, Roche, Louis Coupal: None declared